Pengembangan Desain Multimedia Interaktif Website untuk Memberdayakan Pemecahan Masalah Matematis pada Materi Perbandingan Trigonometri - Ratih Wulandari; Indri Astuti; Afandi Afandi (Departement of Mathematics Education, 2023)
The need for embodiment of progressive learning assisted by educational technology products was needed in the implementation of learning in research locations, departing from the need assessment conducted which shows that the results of previous learning carried out conventionally or not digitally based are classified as not optimal. This research aimed at designing the development of interactive multimedia to empower mathematical problem solving abilities in trigonometry comparison material. The research method used in this study is R&D research which refers to the ADDIE theory by focusing on the Analysis and Design aspects of the ADDIE development model. The ineffectiveness of learning activities carried out previously in the implementation of mathematics learning on trigonometry comparison material, especially in the problem-solving aspect, became the basis for the formation of digital-based learning multimedia development designs, considering that previous learning was carried out conventionally, innovations in making website-based interactive multimedia designs and their application in learning were assessed as the approach used to transition the scale of achievement of academic achievement for students towards a progressive one assisted by educational technology output.